Codon optimality has minimal effect on determining translation efficiency in mycobacterium tuberculosis - Smitha Soman; Somdeb Chattopadhyay; Siya Ram; Vinay Kumar Nandicoori; G. Aneeshkumar Arimbasseri (Scientific Reports, 2023)
Abstract Mycobacterium tuberculosis (Mtb) is a slow-growing, intracellular pathogen that exhibits a high GC-rich genome. Several factors, including the GC content of the genome, influence the evolution of specific codon usage biases in genomes. As a result, the Mtb genome exhibits strong biases for amino acid usage and codon usage. Codon usage of mRNAs affects several aspects of translation, including accuracy, efficiency, and protein folding. Here we address the effect of codon usage biases in determining the translation efficiency of mRNAs in Mtb. Unlike most commonly studied organisms, Mtb carries a single copy of each tRNA gene. However, we show that the relative levels of tRNAs in the Mtb tRNA pool vary by an order of magnitude. Our results show that the codons decoded by the abundant tRNAs indeed show higher adaptability. Moreover, there is a general positive correlation between genomic codon usage and the tRNA adaptability of codons (TAc). We further estimated the optimality of the codon and mRNAs by considering both the TAc and the tRNA demand. These measures did not show any correlation with mRNA abundance and translation efficiency. There was no correlation between tRNA adaptability and ribosome pausing as well. Taken together, we conclude that the translation machinery, and the tRNA pool of an organism, co-evolve with the codon usage to optimize the translation efficiency of an organism. Thus the deleterious effect of maladapted codons is not pronounced.